An informal approach to management development at small and medium-sized manufacturing companies. (2016) - Tell, Joakim
Considerable debate and discussion exist on the effectiveness and relevance of various management development models/approaches/methods intended to support companies and their managers. In recent years management researchers have described successful network collaborations among companies that increase managerial capability, effect positive change, and promote beneficial development. However, the literature has not fully explored the fundamental principles and learning outcomes of learning networks in this context. As a result, organisers (or providers) of management development courses and programs lack the needed resources that help them create effective learning environments. This paper describes an informal management development approach known as the learning network in which SME managers share experiences and ideas in a learning network characterised by mutual trust and purposeful collaboration.